Getting better at sensemaking - Woodside, Arch G. (JAI Press, 2000)
This work's 16 contributions fill the mind with knowledge, skills, and insights useful for improving the executive's ability to do what needs to be done: scan environments better to find the weak signals on breakthrough technologies; understand shifts in customers' attitudes and behaviors; observe changes in behaviors of suppliers, governments, and other stakeholder groups; frame problems/opportunities better by deepening understanding on how we go about making sense of what is happening and can be made to happen; decide better by gaining deep knowledge on how decisions are actually made and can be improved (e.g., via systems thinking and simulating system operations to uncover powerful levers previously unrecognized); and, do better by applying new tools to learn what is really happening when planned strategies are converted into realized strategies.
Keywords: Marketing -- Management.; Perception.; Management & management techniques.; Sales & marketing management.; Business & Economics -- Marketing -- General.; elektronické knihy; electronic books